Hydrogen storage alloy and alkaline storage battery

CN119604635APending Publication Date: 2025-03-11PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380056108.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-05-29
Publication Date
2025-03-11

AI Technical Summary

Benefits of technology

[0026] According to the present disclosure, an alkaline battery having excellent charge and discharge cycle characteristics at very low temperature and high rate discharge characteristics and a hydrogen storage alloy used therein can be obtained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The composition of the disclosed hydrogen storage alloy is represented by the formula LaaR (b-a) MgcZrdNixAlyMz (R is at least one rare earth element including Y but not including La, 0.10 < = a < = 0.40, 0.67 < = b < = 0.96, 0.01 < = c < = 0.30, 0.01 < = d < = 0.05, b + c + d = 1.00, M is at least one element selected from Co, Mn, Ag, and Sn, 3.10 < = x < = 3.80, 0.03 < = y < = 0.25, 0 < = z < = 0.05, and 3.45 < = x + y + z < = 3.85). In the alloy, four phases, each having a Ce2Ni7-type structure, a Ce5Co19-type structure, a Pr5Co19-type structure, and a CaCu5-type structure, are included at a specific ratio as crystal phases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to hydrogen storage alloys and alkaline storage batteries. Background Art

[0002] Alkaline storage batteries such as nickel-metal hydride storage batteries are used for various purposes. Various proposals have been made regarding hydrogen storage alloys used in nickel-metal hydride storage batteries.

[0003] Patent document 1 (Japanese Patent Gazette No. 5171114) discloses: "A hydrogen storage alloy for alkaline storage batteries, characterized in that it is a hydrogen storage alloy for alkaline storage batteries used as a negative electrode active material of alkaline storage batteries, the above hydrogen storage alloy contains, in addition to La, a rare earth element including Y and an element R selected from Group 4, and an element M consisting of at least one of Co, Mn, and Zn, and its general formula is La α R 1-α-β Mg β Ni γ-η-ε Al η M ε (α, β, γ, η, ε are 0≤α≤0.5, 0.1≤β≤0.2, 3.7≤γ≤3.9, 0.1≤η≤0.3, 0≤ε≤0.2), and the crystal structure A5B 19 Type structure is more than 40%, the above A5B 19 The structure is composed of Ce5Co 19 Crystalline phase and Pr5Co 19 Crystalline phase, and contains Ce5Co 19 The crystalline phase is the main body. ".

[0004] Patent document 2 (Japanese Patent Publication No. 2008-084649) discloses: "A hydrogen storage alloy for alkaline storage batteries, characterized in that it is a hydrogen storage alloy for alkaline storage batteries used as a negative electrode active material of alkaline storage batteries, and the above hydrogen storage alloy has at least a Ce2Ni7 type structure and a Ce5Co 19 A mixed phase composed of a type structure. ".

[0005] Patent Document 3 (Japanese Patent Gazette No. 5512080) discloses: "An alkaline storage battery comprising a positive electrode, a negative electrode containing a rare earth-Mg-Ni series hydrogen storage alloy, a separator, and an electrolyte.

[0006] The main crystal structure of the rare earth-Mg-Ni hydrogen storage alloy is a Ce2Ni7 type structure or a similar structure.

[0007] With the general formula: (A α Ln 1-α ) 1-β Mg β Niγ-δ-ε Al δ T ε The composition of the representation,

[0008] (wherein A represents at least one element selected from the group consisting of Pr, Nd, Sm and Gd including at least Sm, Ln represents at least one element selected from the group consisting of La, Ce, Pm, Eu, Tb, Dy, Ho, Er, Tm, Yb, Lu, Sr, Sc, Y, Ti, Zr and Hf, T represents at least one element selected from the group consisting of V, Nb, Ta, Cr, Mo, Mn, Fe, Co, Zn, Ga, Sn, In, Cu, Si, P and B, subscripts α, β, γ, δ and ε represent numbers satisfying 0.4≤α, 0.05<β<0.15, 3.0≤γ≤4.2, 0.15≤δ≤0.30 and 0≤ε≤0.20, respectively, and the amount of Sm in A is at least 35% of the total amount of A). ".

[0009] Patent Document 4 (Japanese Patent No. 6061354) discloses: "A hydrogen storage alloy characterized in that it is a hydrogen storage alloy in which two or more crystal phases having mutually different crystal structures are stacked in the c-axis direction of the crystal structure, and contains Ce5Co 19 The crystalline phase of the Ce5Co 19 phase”.), Ce5Co 19 Phase, Pr5Co 19 The total content of Ce2Ni7 phase, Ce2Ni7 phase and CaCu5 phase is 70 mass % or more, and the CaCu5 phase is 30 mass % or less (including Ce5Co 19 phase is 0), its composition is composed of La h R6 i R7 j Mg k R8' m1 R8” m2 Represents, (wherein, R6 is one or more elements selected from rare earth elements including Y and excluding La, R7 is one or more elements selected from Zr, Ti, Zn, Sn and V, R8' is one or two elements selected from Ni and Co, and R8" is one or two elements selected from Mn and Al, satisfying 11≤h≤16, 0≤i≤6, 0≤j≤0.65, 2≤k≤5.5, 0.70≤h / (h+i)≤0.85, 72≤m1≤77, 3≤m2≤6 (wherein the Mn content is less than 3 mol%), m1+m2=m, h+i+j+k+m=100).".

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent No. 5171114

[0013] Patent Document 2: Japanese Patent Application Publication No. 2008-084649

[0014] Patent Document 3: Japanese Patent No. 5512080

[0015] Patent Document 4: Japanese Patent No. 6061354 Summary of the invention

[0016] In order to improve various properties, a lot of research has been conducted on alloy composition and crystal phase ratio, but the improvement of discharge properties at -10°C is the limit, and it is impossible to improve the discharge properties at extremely low temperatures below that, such as -30°C. In particular, it is completely impossible to make both high-rate discharge properties at -30°C and charge-discharge cycle properties at room temperature good.

[0017] Since alkaline storage batteries are used in various situations, various characteristics are required. For example, in applications such as vehicle-mounted equipment such as vehicle emergency call systems, in recent years, batteries with good characteristics of high-rate discharge at extremely low temperatures (for example, -30°C, 2It (A) discharge) are required. In addition, batteries with good charge and discharge cycle characteristics are required in addition to extremely low-temperature high-rate discharge characteristics.

[0018] One aspect of the present disclosure relates to a hydrogen storage alloy. The composition of the hydrogen storage alloy is represented by the following formula (F):

[0019] La a R (b-a) Mg c Zr d Ni x Al y M z (F)

[0020] (R is at least one rare earth element including Y and excluding La. It satisfies the formulas of 0.10≤a≤0.40, 0.67≤b≤0.96, 0.01≤c≤0.30, 0.01≤d≤0.05, and b+c+d=1.00. M is at least one element selected from Co, Mn, Ag, and Sn. It satisfies 3.10≤x≤3.80, 0.03≤y≤0.25, 0≤z≤0.05, and 3.45≤x+y+z≤3.85.)

[0021] As a crystalline phase, it includes a first phase, a second phase, a third phase and a fourth phase, wherein the first phase is selected from a phase having a Ce2Ni7 type structure, a phase having a Ce5Co 19 Phases with Pr5Co 19The second phase is another phase selected from the above phase group, the third phase is another phase selected from the above phase group, and the fourth phase has a CaCu5-type structure.

[0022] In the above-mentioned crystalline phases, when the composition ratio of the above-mentioned first phase is α (mass %), the composition ratio of the above-mentioned second phase is β (mass %), the composition ratio of the above-mentioned third phase is γ (mass %), and the composition ratio of the above-mentioned fourth phase is δ (mass %),

[0023] Satisfies δ<α, γ≤β≤α, 60≤α+β≤83, α / β≤15.0 and 1≤δ≤15.

[0024] Another aspect of the present disclosure relates to an alkaline storage battery, which comprises a positive electrode, a negative electrode and an alkaline electrolyte, wherein the negative electrode comprises a negative electrode active material, and the negative electrode active material comprises the hydrogen storage alloy according to one aspect of the present disclosure.

[0025] As long as they can be combined, the matters described in two or more claimed technical solutions arbitrarily selected from the plurality of claimed technical solutions described in the attached claims can be combined. In addition, as long as they can be combined, the configurations described in the embodiments can be combined arbitrarily.

[0026] According to the present disclosure, an alkaline storage battery having excellent extremely low temperature high rate discharge characteristics and charge and discharge cycle characteristics at room temperature, and a hydrogen storage alloy used therein can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a partially exploded perspective view schematically showing the alkaline storage battery according to the first embodiment.

[0028] Figure 2 It is a graph showing the evaluation results of the alkaline storage battery according to the first embodiment.

[0029] Figure 3 It is a graph showing the evaluation results of the alkaline storage battery according to the first embodiment.

[0030] Figure 4 It is a graph showing the evaluation results of the alkaline storage battery according to the first embodiment.

[0031] Figure 5 It is a graph showing the evaluation results of the alkaline storage battery according to the first embodiment.

[0032] Figure 6 It is a graph showing the evaluation results of the alkaline storage battery according to the first embodiment.

[0033] Figure 7 It is a graph showing the evaluation results of the alkaline storage battery according to the first embodiment.

[0034] Figure 8 It is a graph showing the evaluation results of the alkaline storage battery according to the first embodiment.

[0035] Fig. 9 It is a graph showing the evaluation results of the alkaline storage battery according to the first embodiment.

[0036] Fig.10 It is a graph showing the evaluation results of the alkaline storage battery according to the first embodiment.

[0037] Fig.11 It is a graph showing the evaluation results of the alkaline storage battery according to the first embodiment.

[0038] Fig.12 It is a graph showing the evaluation results of the alkaline storage battery according to the first embodiment. DETAILED DESCRIPTION

[0039] Hereinafter, embodiments of the present disclosure are illustrated, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values ​​and materials are sometimes illustrated, but other numerical values ​​and other materials may also be applied as long as the invention of the present disclosure can be implemented. In this specification, a description such as "numerical value A to numerical value B" includes numerical value A and numerical value B, and may be replaced by "above numerical value A and below numerical value B". In the following description, when multiple lower limits and multiple upper limits of numerical values ​​related to specific physical properties, conditions, etc. are illustrated, as long as the lower limit is not above the upper limit, any one of the multiple lower limits illustrated and any one of the multiple upper limits illustrated may be arbitrarily selected for combination.

[0040] As described above, alkaline storage batteries having excellent extremely low temperature high rate discharge characteristics and charge-discharge cycle characteristics are currently required. As a result of the research, the inventors of the present application have newly discovered that by using a hydrogen storage alloy having a specific composition and a specific crystal structure, an alkaline storage battery having excellent extremely low temperature high rate discharge characteristics and charge-discharge cycle characteristics can be obtained. The present disclosure is based on this new insight. The present disclosure provides a hydrogen storage alloy having a composition and a composition ratio of a crystal phase that can make both of the above two characteristics good.

[0041] (Hydrogen Storage Alloy)

[0042] Hereinafter, the hydrogen storage alloy of the present embodiment may be referred to as “hydrogen storage alloy (M)”. The hydrogen storage alloy (M) has the following (I) composition and (II) crystal phase.

[0043] (I) Composition

[0044] The composition of the hydrogen storage alloy (M) is represented by the following formula (F).

[0045] La a R(b-a) Mg c Zr d Ni x Al y M z (F)

[0046] (R is at least one rare earth element including Y and excluding La. It satisfies the formulas of 0.10≤a≤0.40, 0.67≤b≤0.96, 0.01≤c≤0.30, 0.01≤d≤0.05, and b+c+d=1.00. M is at least one element selected from Co, Mn, Ag, and Sn. It satisfies 3.10≤x≤3.80, 0.03≤y≤0.25, 0≤z≤0.05, and 3.45≤x+y+z≤3.85.)

[0047] The element R may be composed of only one element or multiple rare earth elements. For example, the element R may be at least one element selected from Sm, Y, Pr and Nd. The element R may be any one element of Sm, Y, Pr and Nd or multiple elements thereof.

[0048] The element M may be any one of Co, Mn, Ag and Sn, or may be a plurality of these elements.

[0049] Examples of the hydrogen storage alloy (M) include hydrogen storage alloys described as examples of the hydrogen storage alloy (M) in the examples described below (eg, powder a1 of the hydrogen storage alloy used in the negative electrode of battery A1, and powder a1′ converted into powder a1 by activation).

[0050] The composition formula of the above powders (powders a1 and a1') of the hydrogen storage alloy is La 0.35 Sm 0.47 Mg 0.15 Zr 0.03 Ni 3.36 Al 0. 09 , the ratio of its crystalline phase is Ce5Co 19 type crystalline phase 38% by mass, Ce2Ni7 type crystalline phase 37% by mass, Pr5Co 19 The combination of these compositions and the ratio of the crystalline phases was achieved for the first time by setting Zr as an essential element, setting the composition ratio of La and Mg to the above range, and setting the heat treatment conditions of the ingot when making the alloy to the specified conditions (e.g., 960°C, 10 hours). The same is true for other hydrogen storage alloys (M) other than powders a1' and a1. These insights are new insights that have not been seen before.

[0051] Furthermore, by using a hydrogen storage alloy (M) such as powder a1, it is possible to achieve effects that were not previously achievable, that is, both high-rate discharge characteristics at extremely low temperatures such as -30°C and charge-discharge cycle life characteristics at room temperature can be improved. The composition and effects of the hydrogen storage alloy powder a1 are insights and effects that were not previously available, and are the first to be discovered by the inventors. The hydrogen storage alloy (such as powder a1) shown in the embodiment is an example of a hydrogen storage alloy (M), and various combinations and patterns may be possible with respect to the composition and the ratio of the crystal phases. These examples include the examples disclosed in this specification, such as the examples described below.

[0052] In the formula (F), 0.01≤c<0.10 (for example, 0.02≤c≤0.09) may be satisfied. By satisfying this formula, the charge-discharge cycle characteristics of the alkaline storage battery can be particularly improved.

[0053] In formula (F), 0.20<c≤0.30 (for example, 0.21≤c≤0.30 or 0.21≤c≤0.28) may be satisfied. By satisfying this formula, the high rate discharge characteristics of the alkaline storage battery at extremely low temperatures can be particularly improved.

[0054] In formula (F), the following condition (1) may be satisfied, condition (2) or (2′) may be satisfied, and condition (3) or (3′) may be satisfied.

[0055] (1) The element R contains Sm or is Sm.

[0056] (2) z = 0.

[0057] (2') 0<z≤0.05 (for example, 0.01≤z≤0.05).

[0058] (3) Satisfying 0.01≤c<0.10 (for example, 0.02≤c≤0.09).

[0059] (3') satisfies 0.10≤c≤0.30 (for example, 0.20<c≤0.30 or 0.21≤c≤0.28).

[0060] In formula (F), the above conditions may be satisfied in any of the following modes.

[0061] Mode a: satisfies conditions (1), (2), and (3).

[0062] Mode b: satisfies conditions (1), (2'), and (3).

[0063] Mode c: satisfies conditions (1), (2'), and (3').

[0064] Mode d: satisfies conditions (1), (2), and (3').

[0065] In the formula (F), x may be 3.30 or more or 3.40 or more, or 3.70 or less or 3.50 or less. In the formula (F), y may be 0.09 or more, or 0.19 or less.

[0066] The composition of the hydrogen storage alloy (M) can be changed by changing the mixing ratio of the materials. For example, the composition of the hydrogen storage alloy (M) can be changed by changing the mixing ratio of the materials when preparing an ingot of the alloy.

[0067] The composition of the hydrogen storage alloy (M) can be determined by ICP emission analysis. ICP emission analysis can be performed using an inductively coupled plasma (ICP) emission spectrophotometer specified in JIS K0116. Specifically, first, the alloy sample is pretreated with an acid (nitric acid, hydrochloric acid, etc.) to obtain a sample solution. Next, the obtained sample solution is sprayed into the plasma torch of the above-mentioned analysis device, and the emission of a specific element is measured. Based on the wavelength and intensity of the emission, the type of element contained in the sample and the amount of the element can be determined.

[0068] (II) Crystalline phase

[0069] The hydrogen storage alloy (M) includes, as a crystalline phase, a phase selected from a phase having a Ce2Ni7 type structure, a phase having a Ce5Co 19 Phases with Pr5Co 19 The first phase, the second phase and the third phase (crystalline phase) in the phase group composed of the phase composition of the CaCu5 type structure, and the fourth phase (crystalline phase) having the CaCu5 type structure.

[0070] In the crystal phase of the hydrogen storage alloy (M), the composition ratio of the first phase is α (mass %), the composition ratio of the second phase is β (mass %), the composition ratio of the third phase is γ (mass %), and the composition ratio of the fourth phase is δ (mass %). At this time, δ<α, γ≤β≤α, 60≤α+β≤83, α / β≤15.0, and 1≤δ≤15 are satisfied.

[0071] In this specification, a phase having a CaCu5 type structure is sometimes referred to as a "CaCu5 type crystalline phase". Similarly, a phase having a Ce2Ni7 type structure, a phase having a Ce5Co2 type structure, and a phase having a Ce5Co2 type structure are sometimes referred to as "CaCu5 type crystalline phase". 19 Phases with Pr5Co 19 The phases with the structure are called "Ce2Ni7 type crystalline phase", "Ce5Co 19 type crystalline phase" and "Pr5Co 19 It should be noted that, in this specification, unless otherwise specified, the composition ratio of the crystal phase refers to the composition ratio expressed in mass %.

[0072] The first phase is Ce2Ni7 type crystal phase, Ce5Co 19 Type crystalline phase and Pr5Co 19 The first phase is the phase with the highest composition ratio among the first phase and the second phase is the phase with the highest composition ratio among the three phases. The second phase is the phase with the composition ratio equal to or lower than that of the first phase among the three phases. The third phase is the phase with the composition ratio equal to or lower than that of the second phase among the three phases. The crystalline phase of the hydrogen storage alloy (M) is usually composed of the first to third phases and the CaCu5 type crystalline phase. The crystalline phase of the hydrogen storage alloy (M) may include a crystalline phase (fifth phase) other than these four phases. However, among the crystalline phases, the composition ratio of the fifth phase is usually lower than that of the third phase.

[0073] The composition ratios α, β, and γ may satisfy γ<β≤α, γ≤β<α, or γ<β<α. α may be 29 or more, 38 or more, or 50 or more, or 77 or less, 65 or less, 55 or less, or 48 or less. β may be 5 or more, 9 or more, or 20 or more, or 37 or less, 27 or less, or 20 or less. γ may be 4 or more, 11 or more, or 17 or more, or 28 or less, 19 or less, or 17 or less. δ may be 1 or more, 4 or more, or 9 or more, or 15 or less, 12 or less, or 8 or less.

[0074] α / β may be 1.0 or more, 4.1 or more, or 7.8 or more, and may be 15.0 or less, 10.7 or less, or 7.8 or less.

[0075] The composition ratios α, β, γ, and δ may satisfy the following pattern.

[0076] Mode A: α is in the range of 70-75, β is in the range of 6-9, γ is in the range of 3-8, and δ is in the range of 11-15.

[0077] Mode B: α is in the range of 60 to 66, β is in the range of 14 to 20, γ is in the range of 8 to 12, and δ is in the range of 8 to 13.

[0078] Mode C: α is in the range of 50-60, β is in the range of 17-28, γ is in the range of 6-20, and δ is in the range of 1-13.

[0079] Mode D: α is in the range of 33-48, β is in the range of 27-37, γ is in the range of 13-26, and δ is in the range of 6-14.

[0080] The crystal structures of the first phase, the second phase, and the third phase may be any of the following modes. For example, when γ<β<α is satisfied, the crystal structures of the first phase, the second phase, and the third phase may be any of the following modes.

[0081] Mode 1: The first phase is Ce5Co 19 type crystalline phase, the second phase is Ce2Ni7 type crystalline phase, and the third phase is Pr5Co 19 Type crystalline phase.

[0082] Mode 2: The first phase is Ce5Co 19 Type crystalline phase, the second phase is Pr5Co 19 type crystalline phase, and the third phase is Ce2Ni7 type crystalline phase.

[0083] Mode 3: The first phase is Ce2Ni7 type crystal phase, and the second phase is Ce5Co 19 Type crystalline phase, the third phase is Pr5Co 19 Type crystalline phase.

[0084] Mode 4: The first phase is Ce2Ni7 type crystalline phase, and the second phase is Pr5Co 19 Type crystalline phase, the third phase is Ce5Co 19 Type crystalline phase.

[0085] Mode 5: Phase 1 is Pr5Co 19 Type crystalline phase, the second phase is Ce5Co 19 type crystalline phase, and the third phase is Ce2Ni7 type crystalline phase.

[0086] Mode 6: Phase 1 is Pr5Co 19 type crystalline phase, the second phase is Ce2Ni7 type crystalline phase, and the third phase is Ce5Co 19 Type crystalline phase.

[0087] When any one of the above-mentioned modes a to d is satisfied, any one of the above-mentioned modes A to D may be further satisfied. In any of these combined modes, any one of the above-mentioned modes 1 to 6 may be satisfied.

[0088] The composition ratio of each crystalline phase can be changed by changing the composition of the hydrogen storage alloy (M) and / or the manufacturing conditions of the hydrogen storage alloy (M). For example, by changing the conditions of the heat treatment of the alloy ingot, the composition ratio of the crystalline phase can be changed. If the temperature of the heat treatment is lowered, it is observed that the A2B7 type crystalline phase (Ce2Ni7 type crystalline phase) is easily formed. If the temperature of the heat treatment is increased, it is observed that the A5B 19 Type crystalline phase (Ce5Co 19 Type crystalline phase, Pr5Co 19 If the heat treatment time is reduced, it is observed that A5B is easily formed. 19 Ce5Co 19 If the heat treatment time is increased, it is observed that A5B is easily formed.19 Pr5Co 19 The trend of the crystalline phase.

[0089] The composition ratio of the crystal phase constituting the hydrogen storage alloy (M) is determined by performing X-ray diffraction measurement on the pulverized alloy powder and analyzing the obtained X-ray diffraction pattern by the Rietveld method. Specific conditions are described in the Examples.

[0090] The mass saturation magnetization of the hydrogen storage alloy (M) can be in the range of 1.0 to 4.0 emu / g. By setting the mass saturation magnetization to this range, an alkaline storage battery with particularly high extremely low temperature high rate discharge characteristics and charge and discharge cycle characteristics can be obtained. The mass saturation magnetization can be in the range of 1.0 to 2.0 emu / g, or in the range of 2.0 to 4.0 emu / g. By setting the mass saturation magnetization to less than 4.0 emu / g, the charge and discharge cycle characteristics of the alkaline storage battery can be improved. By setting the mass saturation magnetization to more than 1.0 emu / g, the extremely low temperature high rate discharge characteristics of the alkaline storage battery can be improved.

[0091] The mass saturation magnetization of the hydrogen storage alloy (M) varies depending on the amount of nickel clusters located on the surface of the hydrogen storage alloy. The nickel clusters on the surface of the alloy particles can be increased by stirring the alloy in an alkaline aqueous solution. In addition, the mass saturation magnetization can be increased by performing initial activation of the battery.

[0092] The mass saturation magnetization was measured using a sample vibration magnetometer (VSM) (VSM-C7-10A, a small fully automatic vibration sample magnetometer manufactured by Toei Industry Co., Ltd.) Specifically, the mass saturation magnetization value was obtained by filling 0.2 g of the hydrogen storage alloy powder into the sample holder of the magnetometer and applying a magnetic field of 10 kOe.

[0093] The hydrogen storage alloy (M) is used as a negative electrode active material in the form of powder (particles). The average particle size of the hydrogen storage alloy (M) can be in the range of 15 to 30 μm. By setting the average particle size to this range, an alkaline storage battery with particularly high extremely low temperature high rate discharge characteristics and charge and discharge cycle characteristics can be obtained. By setting the average particle size to 30 μm or less, the extremely low temperature high rate discharge characteristics of the alkaline storage battery can be improved. By setting the average particle size to 15 μm or more, the charge and discharge cycle characteristics of the alkaline storage battery can be improved. In this specification, the average particle size is the median particle size (D50) at which the cumulative volume becomes 50% in the volume-based particle size distribution. The median particle size is determined using a laser diffraction / scattering particle size distribution measuring device. The average particle size of the hydrogen storage alloy (M) can be adjusted by changing the pulverization conditions of the alloy.

[0094] (An example of a method for producing a hydrogen storage alloy (M))

[0095] An example of a method for producing the hydrogen storage alloy (M) will be described below. It should be noted that the hydrogen storage alloy (M) may be produced by a method other than the method described below.

[0096] The manufacturing method of this example includes a step (i) of manufacturing an ingot of an alloy represented by formula (F) and a step (ii) of heat treating the ingot. The manufacturing method may further include a step (iii) of crushing the ingot to obtain an alloy powder (alloy particles) after step (ii). The manufacturing method may also further include a step (iv) of activating the alloy powder after step (iii). The manufacturing method may further include a step of washing the alloy or alloy powder after any of the above steps. Each step is described below.

[0097] (Process (i))

[0098] Step (i) is a step of alloying the metals constituting the alloy to produce an ingot of an alloy having a composition shown in formula (F). As the metal used as the material, a single metal or an alloy can be used. The alloying method is not limited, and a known alloying method can be used. As the alloying method, a plasma arc melting method, a high-frequency melting method, and a rapid solidification method can be used. These methods can be used alone or in combination. For example, a rapid solidification method and a high-frequency melting method can be combined.

[0099] In step (i), a mixture of alloy materials (single metals of each constituent element) is alloyed by the above-mentioned method or the like. For example, the constituent elements can be alloyed by heating the mixture to melt it. In step (i), when mixing the alloy materials, the mixing ratio of each metal is adjusted so that the hydrogen storage alloy (M) has a desired composition. It should be noted that an alloy of the constituent elements may be used as part of the alloy materials.

[0100] The mixture of materials is melted to obtain an alloy in a molten state, which is solidified to obtain an ingot. The solidification of the alloy can be carried out by cooling the alloy in a molten state. For example, the solidification of the alloy can be carried out by supplying the alloy in a molten state to a container such as a mold and cooling it in the container. From the viewpoint of improving the dispersibility of the constituent elements in the alloy, the supply speed of the alloy in a molten state can be appropriately adjusted. In addition, the cooling speed of the alloy in a molten state can also be appropriately adjusted.

[0101] (Step (ii))

[0102] Step (ii) is a step of heat treating the ingot obtained in step (i). By this heat treatment, the composition ratio of the crystalline phase can be changed. In addition, by heat treatment, the dispersibility of the constituent elements in the hydrogen storage alloy can be easily adjusted, and the hydrogen storage alloy can be easily activated. The heat treatment can be performed, for example, at a temperature in the range of 800 to 1100° C. in an atmosphere of an inert gas (such as argon) for a time in the range of 7 to 13 hours. A preferred example of heat treatment is to perform a time in the range of 900 to 980° C. (for example, a range of 900 to 960° C.) in an atmosphere of an inert gas (such as argon) for a time in the range of 9 to 12 hours. Under this condition, the composition ratio of the above-mentioned crystalline phase can be easily achieved. The temperature of the heat treatment can be in the range of 900 to 980° C., 910 to 980° C., 920 to 980° C., 940 to 980° C., 950 to 980° C., and 960 to 980° C. In any of these ranges, as long as the lower limit is not greater than the upper limit, the upper limit may be set to 980°C, 960°C, or 950°C. In addition, the time of the heat treatment performed within these temperature ranges may be in the range of 7 to 13 hours (e.g., 9 to 12 hours). Thus, an ingot of the hydrogen storage alloy (M) can be obtained.

[0103] (Process (iii))

[0104] Step (iii) is a step of crushing the alloy (ingot) that has passed step (ii) to obtain alloy powder (alloy particles). There is no limitation on the method for crushing the alloy, and a known crushing method can be used. The alloy can be crushed by wet crushing or dry crushing, or a combination of these. The crushing can be carried out using a ball mill, etc. In wet crushing, a liquid medium (water, etc.) is used during crushing. It should be noted that the obtained particles can be classified as needed. By changing the crushing conditions, the average particle size of the alloy particles can be changed. In this way, a powder of the hydrogen storage alloy (M) can be obtained. The powder can be further activated and used as a negative electrode active material.

[0105] (Process (iv))

[0106] Step (iv) is a step of activating the alloy powder (alloy particles) obtained in step (iii). Activation can be performed by contacting the alloy powder with an alkaline aqueous solution. The method of contacting the alloy powder with the alkaline aqueous solution is not particularly limited. For example, the alloy powder can be immersed in an alkaline aqueous solution, or the alloy powder can be added to the alkaline aqueous solution and stirred. Activation can be performed under heating as required. It should be noted that activation can also be performed using an acidic aqueous solution instead of an alkaline aqueous solution. It can also be performed using an acidic aqueous solution after using an alkaline aqueous solution.

[0107] As the alkaline aqueous solution, for example, an aqueous solution containing an alkali metal hydroxide (potassium hydroxide, sodium hydroxide, lithium hydroxide, etc.) as the alkali can be used. As the alkali metal hydroxide, sodium hydroxide and / or potassium hydroxide are preferably used. From the viewpoint of activation efficiency, etc., the concentration of the alkali in the alkaline aqueous solution can be in the range of 5 to 50 mass % (for example, in the range of 10 to 45 mass %).

[0108] The alloy powder after activation treatment with an alkaline aqueous solution may be washed with water. The alloy powder after activation treatment is usually dehydrated. In order to reduce impurities remaining on the surface of the alloy powder, water washing is preferably performed until the pH of the water used in washing becomes 9 or less. The alloy powder after activation (or after activation and washing) can also be used as a powder of the hydrogen storage alloy (M).

[0109] Thus, a powder of the hydrogen storage alloy (M) can be obtained. The obtained alloy powder can be used as a negative electrode active material for a nickel-hydrogen storage battery. As described later, by using the hydrogen storage alloy (M) as a negative electrode active material, an alkaline storage battery (nickel-hydrogen storage battery) having excellent extremely low temperature high rate discharge characteristics and charge and discharge cycle characteristics can be obtained.

[0110] (Alkaline storage battery)

[0111] Hereinafter, the alkaline storage battery of the present embodiment may be referred to as "alkaline storage battery (A)". The alkaline storage battery (A) includes a positive electrode, a negative electrode containing a negative electrode active material, and an alkaline electrolyte. The negative electrode active material includes the above-mentioned hydrogen storage alloy (M). As described above, the hydrogen storage alloy (M) is omitted for repeated description.

[0112] The alkaline storage battery (A) is, for example, a nickel-metal hydride storage battery containing nickel hydroxide as a positive electrode active material. Therefore, in this specification, the alkaline storage battery (A) can be replaced by "nickel-metal hydride storage battery (A)". As shown in the examples, the alkaline storage battery (A) has good extremely low temperature high rate discharge characteristics and good charge and discharge cycle characteristics. Such an alkaline storage battery (A) can be preferably used for applications such as high rate discharge at extremely low temperatures. For example, the alkaline storage battery (A) can be preferably used as a battery for vehicle use.

[0113] In the alkaline storage battery (A), potassium hydroxide (KOH) is preferably dissolved in the alkaline electrolyte. By dissolving potassium hydroxide, an aqueous solution with high conductivity can be obtained. The potassium concentration of the alkaline electrolyte (more specifically, the concentration of potassium ions) can be in the range of 5.5 to 8.0 mol / L. By setting it to this range, the extremely low temperature high rate discharge characteristics and the charge and discharge cycle characteristics can be particularly improved. By making the potassium concentration of the alkaline electrolyte less than 8.0 mol / L, the charge and discharge cycle characteristics can be improved. By making the potassium concentration more than 5.5 mol / L, the extremely low temperature high rate discharge characteristics can be improved.

[0114] (Method for producing alkaline storage battery (A))

[0115] The manufacturing method of the alkaline storage battery (A) is not particularly limited except for using the hydrogen storage alloy (M), and a known manufacturing method can be used. In one example of a manufacturing method, first, an electrode group is formed by a positive electrode, a negative electrode, and a separator. Next, the electrode group and the electrolyte are placed in an outer casing. In this way, an alkaline storage battery can be manufactured.

[0116] The following describes the configuration and components of the alkaline storage battery (A). However, the configuration and components of the alkaline storage battery (A) are not limited to the following examples. Components other than the hydrogen storage alloy (M) may be known components used in alkaline storage batteries (e.g., nickel-metal hydride storage batteries).

[0117] An example of an alkaline storage battery (A) includes an outer body, an electrode group housed in the outer body, and an alkaline electrolyte. The shape of the electrode group is not limited, and it can be a wound body or a shape other than a wound body (such as a laminate). The electrode group of the wound body is formed by winding a positive electrode, a negative electrode, and a separator so that the separator is arranged between the positive electrode and the negative electrode. The electrode group of the laminate is formed by stacking a positive electrode, a negative electrode, and a separator so that the separator is arranged between the positive electrode and the negative electrode. The shape of the alkaline storage battery (A) is not limited, and it can be cylindrical, square, or button-shaped (including coin-shaped), etc.

[0118] (positive electrode)

[0119] The positive electrode is not particularly limited, and a positive electrode used in a known nickel-metal hydride storage battery can be used. The positive electrode includes a positive electrode mixture containing a positive electrode active material. The positive electrode can include a positive electrode collector and a positive electrode mixture (positive electrode mixture layer) supported by the positive electrode collector. The positive electrode can be a paste-type positive electrode.

[0120] The positive electrode current collector is not particularly limited, and a known positive electrode current collector can be used. Examples of positive electrode current collectors include porous current collectors formed of metal (nickel or nickel alloy, etc.). Specifically, examples of positive electrode current collectors include nickel foam and sintered nickel plate, etc.

[0121] The positive electrode mixture contains particles of a nickel compound (positive electrode active material) and may contain other components (conductive material, binder, thickener, etc.) as required. The particles of the nickel compound may be particles of a known nickel compound (e.g., nickel hydroxide) used in alkaline storage batteries. A portion of the nickel hydroxide in the positive electrode mixture may also be changed to nickel oxyhydroxide.

[0122] The particles of the nickel compound may contain trace components other than nickel hydroxide and nickel oxyhydroxide. The surface of the particles of the nickel compound may be coated with other compounds. Examples of compounds used for such coating include metal hydroxides, etc. Specifically, examples of compounds used for coating include cobalt hydroxide, γ-cobalt oxyhydroxide, β-cobalt oxyhydroxide, etc.

[0123] The conductive material is not particularly limited, and known conductive materials can be used. Examples of conductive materials include conductive fibers such as metal fibers; metal particles such as nickel powder and cobalt powder, etc. These conductive materials can be used alone or in combination of two or more. As the conductive material, conductive cobalt compounds (cobalt hydroxide, γ-type cobalt oxyhydroxide, etc.) can be used.

[0124] The amount of the conductive material may be in the range of 0.01 to 20 parts by mass (eg, in the range of 0.1 to 10 parts by mass) relative to 100 parts by mass of the active material.

[0125] The conductive material can be added to the positive electrode paste and mixed with other ingredients. In addition, the surface of the active material particles can be pre-coated with the conductive material. There is no limitation on the method of coating with the conductive material, and a known method can be used. For example, the coating can be performed by applying the conductive material on the surface of the active material particles. Alternatively, the coating can be performed by attaching a dispersion containing the conductive material to the surface of the active material particles and drying it. Alternatively, the coating can be performed by a mechanochemical method or the like.

[0126] The binder is not particularly limited, and known binders used in alkaline storage batteries can be used. Examples of binders include rubber-like materials such as styrene-butadiene copolymer rubber; polyolefin resins such as polyethylene and polypropylene; fluororesins such as polyvinylidene fluoride; acrylic resins such as ethylene-acrylic acid copolymers and ethylene-methyl acrylate copolymers, and Na ion crosslinked bodies thereof. These binders can be used alone or in combination of two or more. The amount of the binder can be 7 parts by mass or less, or can be in the range of 0.01 to 5 parts by mass relative to 100 parts by mass of the positive electrode active material.

[0127] Examples of thickeners include carboxymethyl cellulose and its modified forms (including sodium salts, ammonium salts, etc.), cellulose derivatives such as methyl cellulose; saponified polymers having vinyl acetate units such as polyvinyl alcohol; polyalkylene oxides such as polyethylene oxide, etc. These thickeners can be used alone or in combination of two or more. The amount of the thickener can be 5 parts by mass or less, or in the range of 0.01 to 3 parts by mass, relative to 100 parts by mass of the positive electrode active material.

[0128] The positive electrode can be formed by attaching a positive electrode mixture containing a positive electrode active material to a positive electrode collector. When manufacturing a positive electrode, the positive electrode mixture is usually used in the form of a paste containing a dispersion medium. In one example of a method for manufacturing a positive electrode, first, a positive electrode paste containing a positive electrode active material is prepared. Next, the positive electrode paste is applied or filled on a positive electrode collector, followed by drying and rolling. Thus, a positive electrode comprising a positive electrode collector and a positive electrode mixture layer supported by the positive electrode collector can be manufactured.

[0129] (negative electrode)

[0130] The negative electrode is not particularly limited except that it contains a hydrogen storage alloy (M) as a negative electrode active material. Constituent elements other than the negative electrode active material can use the constituent elements of the negative electrode used in a known nickel-hydrogen storage battery. In one aspect, the present disclosure provides a negative electrode containing a hydrogen storage alloy (M) as a negative electrode active material. The negative electrode can be used as a negative electrode of an alkaline storage battery (specifically, a nickel-hydrogen storage battery).

[0131] The negative electrode may include a negative electrode current collector and a negative electrode mixture layer supported by the negative electrode current collector. The negative electrode current collector is not limited, and a known negative electrode current collector may be used. Examples of negative electrode current collectors include porous or non-porous metal (stainless steel, nickel, nickel alloy, etc.) sheets.

[0132] The negative electrode can be formed by attaching a negative electrode mixture containing a negative electrode active material to a negative electrode collector. When manufacturing a negative electrode, the negative electrode mixture is usually used in the form of a paste containing a dispersion medium. In one example of a method for manufacturing a negative electrode, first, a negative electrode paste containing a powder of a hydrogen storage alloy (M) is prepared. Next, the negative electrode paste is applied or filled on a negative electrode collector, followed by drying and rolling. In this way, a negative electrode including a negative electrode collector and a negative electrode mixture layer supported by the negative electrode collector can be manufactured.

[0133] The negative electrode mixture may contain components other than the negative electrode active material (conductive agent, binder, thickener, etc.) as needed. The dispersion medium, conductive material, binder and thickener may use the same substances as those exemplified for the positive electrode. The amount of the conductive material, binder and thickener relative to 100 parts by mass of the negative electrode active material may be within the range exemplified as the amount relative to 100 parts by mass of the positive electrode active material.

[0134] (Alkaline electrolyte)

[0135] As the alkaline electrolyte, an aqueous solution containing an alkaline solute can be used. Examples of the solute include alkali metal hydroxides, specifically, lithium hydroxide, potassium hydroxide, sodium hydroxide, etc. The solute can be used alone or in combination of two or more.

[0136] The concentration of the solute (specifically, alkali metal hydroxide) contained in the alkaline electrolyte may be in the range of 2.5 to 13 mol / L (eg, 3 to 12 mol / L). The specific gravity of the alkaline electrolyte may be in the range of 1.1 to 1.6 (eg, 1.2 to 1.5).

[0137] As mentioned above, the alkaline electrolyte preferably contains potassium hydroxide. The alkaline electrolyte may contain potassium hydroxide and other alkali metal hydroxides (lithium hydroxide and / or sodium hydroxide). The alkaline electrolyte may contain only potassium hydroxide as a solute, or may contain potassium hydroxide and sodium hydroxide.

[0138] (Diaphragm)

[0139] The separator is not particularly limited, and a known separator used in an alkaline storage battery (e.g., a nickel-metal hydride storage battery) can be used. Examples of the form of the separator include a microporous film, a nonwoven fabric, and a woven fabric. The separator can be formed of a material having insulating properties. Examples of the material of the separator include polyolefin resins such as polyethylene and polypropylene; fluororesins; polyamide resins, etc.

[0140] (other)

[0141] The components other than the above (external body, lead wire, etc.) are not particularly limited, and known components used in alkaline storage batteries (e.g., nickel-metal hydride storage batteries) can be used. In the case where the alkaline storage battery (A) is a cylindrical battery, an external body in one example includes a bottomed cylindrical battery case, a sealing body for sealing the battery case, and a gasket.

[0142] Hereinafter, an example of the present embodiment will be described in detail with reference to the accompanying drawings. The constituent elements of the embodiment of the example described below can be applied to the above constituent elements. In addition, the constituent elements of the embodiment of the example described below can be changed based on the above description. In addition, the matters described below can be applied to the above embodiment. In addition, in the embodiment of the example described below, constituent elements that are not essential in the alkaline storage battery of the present disclosure can also be omitted.

[0143] (Implementation method 1)

[0144] The alkaline storage battery 10 of the first embodiment is shown in Figure 1 The alkaline storage battery 10 is a nickel-metal hydride storage battery.

[0145] Figure 11 is a partially exploded perspective view schematically showing the structure of an alkaline storage battery 10. The alkaline storage battery 10 includes a battery case 4 and an electrode group and an alkaline electrolyte 11 housed in the battery case 4. The battery case 4 is a bottomed cylindrical case. The electrode group is formed by winding a negative electrode 1, a positive electrode 2, and a separator 3 so that the separator 3 is arranged between the negative electrode 1 and the positive electrode 2. The opening of the battery case 4 is sealed by a sealing body 7 and an insulating gasket 8. The sealing body 7 includes a positive terminal 5 and a safety valve 6. The positive electrode 2 is electrically connected to the sealing body 7 via a positive electrode collector plate 9. The battery case 4 is electrically connected to the negative electrode 1 and functions as a negative terminal.

[0146] The negative electrode 1 includes a negative electrode current collector and a negative electrode mixture layer disposed on the negative electrode current collector. The negative electrode mixture layer includes powder of a hydrogen storage alloy (M) as a negative electrode active material.

[0147] (Note)

[0148] The following techniques are disclosed through the description of the above embodiments.

[0149] (Technique 1) A hydrogen storage alloy having a composition represented by the following formula (F):

[0150] La a R (b-a) Mg c Zr d Ni x Al y M z (F)

[0151] (R is at least one rare earth element including Y and excluding La. It satisfies the formulas of 0.10≤a≤0.40, 0.67≤b≤0.96, 0.01≤c≤0.30, 0.01≤d≤0.05, and b+c+d=1.00. M is at least one element selected from Co, Mn, Ag, and Sn. It satisfies 3.10≤x≤3.80, 0.03≤y≤0.25, 0≤z≤0.05, and 3.45≤x+y+z≤3.85.)

[0152] As a crystalline phase, it includes a first phase, a second phase, a third phase and a fourth phase, wherein the first phase is selected from a phase having a Ce2Ni7 type structure, a phase having a Ce5Co 19 Phases with Pr5Co 19The second phase is another phase selected from the phase group, the third phase is another phase selected from the phase group, the fourth phase has a CaCu5 type structure, and in the above-mentioned crystalline phases, when the composition ratio of the first phase is α (mass %), the composition ratio of the second phase is β (mass %), the composition ratio of the third phase is γ (mass %), and the composition ratio of the fourth phase is δ (mass %),

[0153] Satisfies δ<α, γ≤β≤α, 60≤α+β≤83, α / β≤15.0 and 1≤δ≤15.

[0154] (Technique 2)

[0155] According to the hydrogen storage alloy described in the technique 1, in the above formula (F), 0.01≤c<0.10 is satisfied.

[0156] (Technique 3)

[0157] According to the hydrogen storage alloy described in the technique 1, in the above formula (F), 0.20<c≤0.30 is satisfied.

[0158] (Technique 4)

[0159] According to any one of the techniques 1 to 3, the hydrogen storage alloy has an average particle size in the range of 15 to 30 μm.

[0160] (Technique 5)

[0161] An alkaline storage battery comprises a positive electrode, a negative electrode and an alkaline electrolyte, wherein the negative electrode comprises a negative electrode active material, and the negative electrode active material comprises the hydrogen storage alloy described in any one of technologies 1 to 4.

[0162] (Technique 6)

[0163] According to the alkaline storage battery described in technology 5, potassium hydroxide is dissolved in the alkaline electrolyte.

[0164] The potassium concentration of the alkaline electrolyte is in the range of 5.5 to 8.0 mol / L.

[0165] (Technique 7)

[0166] According to the alkaline storage battery described in technology 5 or 6, the mass saturation magnetization of the above-mentioned hydrogen storage alloy is in the range of 1.0 to 4.0 emu / g.

[0167] <Example>

[0168] The present disclosure will be described in more detail below by way of examples. In the following examples, a plurality of nickel-metal hydride storage batteries were produced and evaluated. Figures 2 to 121 is a diagram showing evaluation results of these storage batteries according to the first embodiment.

[0169] (Experimental Example 1)

[0170] In Experimental Example 1, various nickel-metal hydride storage batteries were produced by changing the hydrogen storage alloy (negative electrode active material). Specifically, the following steps were followed to produce batteries having the same Figure 1 The structure shown is similar to the structure of a nickel-metal hydride storage battery (battery A1).

[0171] (Production of Battery A1)

[0172] (1) Preparation of hydrogen storage alloy

[0173] A hydrogen storage alloy used as a negative electrode active material of battery A1 was produced in the following steps.

[0174] (1-a) Preparation of alloy ingots

[0175] The metals to be the raw materials of the alloy (single substances of La, Sm, Mg, Zr, Ni and Al) are mixed so that a to d and x to z in formula (F) become Figure 2 The mixture was obtained by melting in a high-frequency melting furnace and then cooling, thereby obtaining an ingot of a hydrogen storage alloy.

[0176] (1-b) Heat treatment and crushing of ingots

[0177] The obtained ingot was heat treated at 960°C for 10 hours in an argon atmosphere. The heat-treated ingot was crushed into coarse particles. The obtained coarse particles were crushed into powder in the presence of water using a wet ball mill to obtain a wet powder. The powder was sieved with a sieve with a mesh diameter of 75 μm. Thus, a hydrogen storage alloy powder (powder a1') with an average particle size of 21.2 μm was obtained.

[0178] (1-c) Composition analysis of hydrogen storage alloys and structural analysis of the crystalline phase

[0179] The composition of powder a1' and the structural analysis of the crystalline phase were performed by the following method. As described above, the composition of the hydrogen storage alloy was obtained by ICP emission analysis. In addition, the composition ratio of the crystalline phase of the hydrogen storage alloy was obtained by performing X-ray diffraction measurement and analyzing the obtained X-ray diffraction pattern using the Rietveld method. Specifically, the obtained hydrogen storage alloy was crushed with a mortar, and the crushed alloy was measured using a powder X-ray diffraction device (manufactured by Bruker AXS, D8Advance). The measurement conditions were set to a divergence slit of 0.5 deg., a scattering slit of None, a light receiving slit of 0.1 mm, an X-ray source of Cu-Kα rays, a tube voltage of 40 kV, and a tube current of 40 mA. It should be noted that the diffraction angle is in the range of 2θ=10.0~90.0°, the counting time is 3 seconds, and the scanning step is 0.020°. Based on the obtained X-ray diffraction results, the structure was analyzed by the Rietveld method (using High Score Plus Ver. 4.8 made by PANalytical). This structural analysis revealed the composition ratio of the crystal phases constituting the hydrogen storage alloy.

[0180] The composition of the powder of the hydrogen storage alloy obtained by the above process is as follows: Figure 2 The composition ratio of the crystal phase is represented by the formula (F) shown in FIG. Figure 3 That is, the powder a1' is a powder of the hydrogen storage alloy (M).

[0181] (1-d) Activation and cleaning of powder

[0182] The powder obtained in (1-b) above was mixed with an alkaline aqueous solution (temperature: 100°C) and stirred for 50 minutes to activate the alloy powder. The alkaline aqueous solution used was an alkaline aqueous solution with a potassium hydroxide concentration of 40% by mass. Next, the activated alloy powder was recovered, washed with warm water, and dehydrated. The washing was performed until the pH of the warm water after use became 9 or less. As a result, an alloy powder in a state where impurities were removed was obtained. Thus, powder a1 of the hydrogen storage alloy (hydrogen storage alloy (M)) used in the negative electrode active material of battery A1 was obtained.

[0183] (1-e) Determination of average particle size of hydrogen storage alloy powder

[0184] The average particle size (D50) of the obtained powder a1 was measured using a laser diffraction / scattering particle size distribution analyzer.

[0185] (2) Preparation of negative electrode

[0186] First, a hydrogen storage alloy was prepared according to the following steps. 100 parts by mass of hydrogen storage alloy powder a1, 0.2 parts by mass of carboxymethyl cellulose (thickener), 0.2 parts by mass of Ketjen black (conductive material), and 0.5 parts by mass of styrene butadiene rubber (binder) were mixed to obtain a mixture. Water was added to the obtained mixture and further mixed to prepare a negative electrode paste.

[0187] Next, the negative electrode paste is applied to both sides of the negative electrode collector to form a coating. The negative electrode collector uses a punching metal made of iron that has been plated with nickel. After the obtained coating is dried, it is pressed together with the negative electrode collector to form a negative electrode mixture layer. The negative electrode mixture layer is formed in a manner that has substantially the same thickness in the entire negative electrode. Next, the sheet consisting of the negative electrode collector and the negative electrode mixture layer is cut into a specified size, thereby obtaining a negative electrode.

[0188] (3) Preparation of positive electrode

[0189] First, a positive electrode paste is prepared by mixing nickel hydroxide particles with a predetermined amount of water. Next, the positive electrode paste is filled into a sheet of a foamed nickel porous body (positive electrode current collector) and dried. The resulting sheet is compressed in the thickness direction and cut into a predetermined size to produce a positive electrode.

[0190] (4) Production of alkaline storage batteries

[0191] The positive electrode and negative electrode thus prepared were wound together with a separator to prepare a wound body (electrode group). A nonwoven fabric made of sulfonated polypropylene was used as the separator.

[0192] Next, the winding body and the alkaline electrolyte are placed in the battery case. The alkaline electrolyte uses an electrolyte with an alkali hydroxide concentration of 7.5 mol / L. As for the alkali hydroxide, KOH, NaOH and LiOH are mixed at a molar ratio of KOH:NaOH:LiOH=7.0:0.2:0.3. The potassium concentration in the alkaline electrolyte is set to 7.0 mol / L. The alkaline electrolyte is injected into the battery case in such a way that the positive electrode capacity becomes 2.1 cc per 1 Ah.

[0193] Next, the opening of the battery case was sealed with a gasket and a sealing body. At this time, the foamed nickel porous body (positive electrode current collector) and the sealing body (positive electrode terminal) were electrically connected via a connecting member. In addition, the negative electrode and the battery case (negative electrode terminal) were electrically connected via a connecting member. Thus, an alkaline storage battery (battery A1) was manufactured.

[0194] (Other batteries)

[0195] The battery was produced by the same method and conditions as battery A1, except that the powder of hydrogen storage alloy (negative electrode active material) was different. Figure 2 As for the powder of hydrogen storage alloy, except that a to d and x to y in formula (F) are Figure 2 The powder a1 was prepared by the same method and conditions as the method for preparing the powder a1, except that the ingot was prepared in the manner of the values ​​shown. The powder of the hydrogen storage alloy was evaluated in the same manner as the powder a1' before activation.

[0196] A negative electrode was produced by the same method as that of the negative electrode of battery A1 except that the produced alloy powder was used as the negative electrode active material. Then, another battery (nickel-metal hydride storage battery) was produced by the same method as that of the negative electrode of battery A1 using the negative electrode.

[0197] As described above, a plurality of AA-size alkaline storage batteries (nickel-metal hydride storage batteries) having a theoretical capacity of 1200 mAh were produced. The produced batteries were activated by charging and discharging 10 times in an atmosphere at 50° C., and then the following evaluations were performed.

[0198] (1) High rate discharge test at low temperature (-10℃, 2It(A))

[0199] The high-rate discharge test at low temperature is carried out according to the following steps. First, the battery is charged at a current value of 0.5It (A) for 2 hours and 24 minutes in an atmosphere of 20°C (charging control: -dV = 5mV). Next, the battery is placed in an atmosphere of -10°C for 3 hours. Next, in an atmosphere of -10°C, the battery is discharged at a current value of 2It (A) until the battery voltage becomes 0.8V. The discharge time at this time is taken as the low-temperature discharge characteristic (minutes). The longer the discharge time of the high-rate discharge at low temperature, the better the high-rate discharge characteristics at low temperature. Here, It (A) = 1200mA (theoretical capacity / h).

[0200] (2) High rate discharge test at extremely low temperature (-30°C, 2It (A))

[0201] The high-rate discharge test at extremely low temperatures is carried out according to the following steps. First, the battery is charged at a current value of 0.5It (A) for 2 hours and 24 minutes in an atmosphere of 20°C (charging control: -dV=5mV). Next, the battery is placed in an atmosphere of -30°C for 3 hours. Next, in an atmosphere of -30°C, the battery is discharged at a current value of 2It (A) until the battery voltage becomes 0.8V. The discharge time at this time is taken as the extremely low temperature discharge characteristic (minutes). The longer the discharge time of the high-rate discharge at extremely low temperatures, the better the high-rate discharge characteristics at extremely low temperatures.

[0202] (3) Charge and discharge cycle test at room temperature

[0203] The charge-discharge cycle test at room temperature (20° C.) was performed according to the following procedure. First, a charge-discharge cycle was repeated, wherein one cycle consisted of the following charge step, rest step, and discharge step.

[0204] Charging process: The battery was charged at a current value of 1 It (A) for 1 hour and 12 minutes in an atmosphere at 20° C. (charging control: -dV=5 mV).

[0205] Resting process: The battery was placed in an atmosphere of 20°C for 30 minutes.

[0206] Discharge step: In an atmosphere at 20° C., the battery was discharged at a current value of 1 It (A) until the battery voltage reached 1.0 V. Then, the discharge capacity in this discharge step was measured.

[0207] The initial discharge capacity of the charge-discharge cycle test is defined as 100%, and the number of cycles at which the discharge capacity can be maintained at 60% or more is defined as the number of cycles N. The greater the number of cycles N of the charge-discharge cycle test, the better the charge-discharge cycle characteristics.

[0208] Part of the preparation conditions and evaluation results of the hydrogen storage alloy used in the negative electrode of each battery, and the evaluation results of the battery are shown in Figure 2 to Figure 5 .exist Figure 4 and Figure 5 The results of battery A1 are also shown in the table below. In some cases, CaCu5 type crystal phase, Ce2Ni7 type crystal phase, Ce5Co 19 Type crystalline phase and Pr5Co 19 The crystalline phases of the type are represented as CaCu5, Ce2Ni7, Ce5Co19 and Pr5Co19 respectively. In the following table, the value of the column (ba) represents the composition ratio of Sm, Y, Pr and Nd in formula (F). For example, the composition of the hydrogen storage alloy used in battery A7 is La 0.08 Sm 0.55 Pr 0.10 Mg 0.24 Zr 0.03 Ni 3.43 Al 0.19 Similarly, the values ​​in the column of z represent the composition ratios of Co, Mn, Ag, and Sn in formula (F).

[0209] In the following table, the low-temperature discharge characteristics and the extremely low-temperature discharge characteristics are preferably 10 minutes or more, and the number of cycles N (charge and discharge cycle characteristics) is preferably 1000 cycles or more. It should be noted that the extremely low-temperature discharge characteristics of "0 minutes" means that discharge at extremely low temperatures is impossible (the same applies to the tables described later).

[0210] Batteries A1 to A25 are alkaline storage batteries (A) using hydrogen storage alloys (M). Batteries R1 to R19 are batteries of comparative examples. Figure 3 and Figure 5 As shown, the alkaline storage battery (A) is excellent in both extremely low temperature high rate discharge characteristics and charge and discharge cycle characteristics.

[0211] (Experimental Example 2)

[0212] In Experimental Example 2, various hydrogen storage alloy powders were prepared by the same method and conditions as those for preparing the hydrogen storage alloy powder a1 in Experimental Example 1 except that some conditions were changed. Specifically, the heat treatment conditions of the alloy ingot were as follows: Figure 6 In Experimental Example 2, the heat treatment of the ingot was carried out in an argon atmosphere in the same manner as in the preparation of the powder a1, and the heat treatment temperature and / or heat treatment time were set to Figure 6 The composition of the hydrogen storage alloy was the same as that of the hydrogen storage alloy used in the battery A20. The hydrogen storage alloy powder was evaluated in the same manner as in Experimental Example 1 before activation.

[0213] A plurality of batteries (nickel-metal hydride storage batteries) were produced by the same method and conditions as those for producing battery A1 except that the obtained hydrogen storage alloy powder was used as the negative electrode active material.

[0214] Part of the preparation conditions and evaluation results of the hydrogen storage alloy and the evaluation results of the battery are shown in Figure 6 and Figure 7 It should be noted that Figure 6 and Figure 7 The results for battery A20 are also shown.

[0215] Batteries A20 and A20a to A20f are alkaline storage batteries (A) using hydrogen storage alloys (M). Batteries R20 to R24 are batteries of comparative examples. Figure 7 As shown, the alkaline storage battery (A) is excellent in both extremely low temperature high rate discharge characteristics and charge and discharge cycle characteristics.

[0216] (Experimental Example 3)

[0217] In Experimental Example 3, a plurality of batteries (nickel-metal hydride storage batteries) were produced by the following method.

[0218] (Batteries B1 to B4)

[0219] In addition to Figure 8In addition to changing the mass saturation magnetization of the hydrogen storage alloy powder as shown in the figure, various hydrogen storage alloy powders were produced by the same method and conditions as the production of the hydrogen storage alloy powder a1 of Experimental Example 1. The mass saturation magnetization of the hydrogen storage alloy powder was changed by treating the alloy powder with an alkaline aqueous solution and then adding an acidic aqueous solution for stirring. At this time, by changing the stirring time, the Figure 8 The magnetic susceptibility of the alloy powder was changed as shown. The composition of the alloy powder was the same as that of the powder a1. In addition, even if the mass saturation magnetization was changed, the composition ratio of the crystal phase was substantially the same as that of the powder a1.

[0220] The average particle size (D50) of the obtained hydrogen storage alloy powder was measured by the above method. In addition, the mass saturation magnetization of the obtained hydrogen storage alloy powder was measured by the above method.

[0221] Batteries B1 to B4 (nickel-metal hydride storage batteries) were produced by the same method and conditions as those for producing battery A1 except that the obtained hydrogen storage alloy powder was used as the negative electrode active material.

[0222] (Batteries C1 to C4)

[0223] In addition to changing the average particle size of the hydrogen storage alloy powder, various hydrogen storage alloy powders were produced by the same method and conditions as those for producing the hydrogen storage alloy powder a1 of Experimental Example 1. The average particle size of the hydrogen storage alloy powder was changed by changing the conditions of the pulverizing process. The composition of the alloy powder was the same as that of the powder a1. In addition, even if the average particle size was changed, the composition ratio of the crystalline phase was approximately the same as that of the powder a1. The average particle size (D50) of the produced hydrogen storage alloy was measured by the above method. In addition, for the obtained hydrogen storage alloy powder, the mass saturation magnetization was measured by the above method. It should be noted that the mass saturation magnetization changes not only according to the treatment in the alkaline aqueous solution, but also according to the average particle size.

[0224] Batteries C1 to C4 (nickel-metal hydride storage batteries) were produced by the same method and conditions as those for producing battery A1 except that the obtained hydrogen storage alloy powder was used as the negative electrode active material.

[0225] (Batteries D1 to D4)

[0226] In addition to Figure 8Batteries D1 to D4 (nickel-metal hydride storage batteries) were produced by the same method and conditions as those for producing battery A1, except that the potassium concentration (K concentration) of the alkaline electrolyte was changed as shown. The K concentration was changed by changing the amount of KOH dissolved in the alkaline electrolyte. The powder a1 used in producing battery A1 was used as the negative electrode active material. The obtained batteries were evaluated in the same manner as in Experimental Example 1.

[0227] Part of the evaluation results of the hydrogen storage alloy, the K concentration in the electrolyte, and the evaluation results of the battery are shown in Figure 8 It should be noted that Figure 8 The results for battery A1 are also shown.

[0228] Figure 8 The battery shown is an alkaline storage battery (A) using a hydrogen storage alloy (M). Comparison of batteries B1 to B4 shows that by setting the mass saturation magnetization of the hydrogen storage alloy to a range of 1.0 to 4.0 emu / g, a battery having particularly excellent extremely low temperature high rate discharge characteristics and charge and discharge cycle characteristics can be obtained.

[0229] Comparison of Batteries C1 to C4 revealed that by setting the average particle size of the hydrogen storage alloy in the range of 15 to 30 μm, a battery having particularly excellent extremely low temperature high rate discharge characteristics and charge and discharge cycle characteristics can be obtained.

[0230] Comparison of Batteries D1 to D4 revealed that a battery having particularly excellent extremely low-temperature high-rate discharge characteristics and charge-discharge cycle characteristics can be obtained by setting the K concentration in the alkaline electrolyte to a range of 5.5 to 8.0 mol / L.

[0231] (Experimental Example 4)

[0232] In Experimental Example 4, various hydrogen storage alloy powders were prepared by the same method and conditions as those for preparing the hydrogen storage alloy powder a1 in Experimental Example 1 except that some conditions were changed. Specifically, the alloy composition and the conditions for heat treatment of the ingot were changed to Fig. 9 The hydrogen storage alloy powder was prepared by changing the conditions as shown in the figure. The hydrogen storage alloy powder was evaluated by the same method as in Experimental Example 1 at the stage before activation.

[0233] Batteries R25 to R28 (nickel-metal hydride storage batteries) were produced by the same method and conditions as those for producing battery A1, except that the produced hydrogen storage alloy powder was used as the negative electrode active material.

[0234] Part of the preparation conditions and evaluation results of the hydrogen storage alloy and the evaluation results of the battery are shown in Fig. 9 It should be noted that Fig. 9 The results for battery A1 are also shown.

[0235] Batteries R25 to R28 are batteries of comparative examples. Fig.10 As shown, the battery of the comparative example has low extremely low temperature high rate discharge characteristics and low charge and discharge cycle characteristics.

[0236] (Experimental Example 5)

[0237] In Experimental Example 5, various hydrogen storage alloy powders were prepared by the same method and conditions as those for preparing the hydrogen storage alloy powder a1 in Experimental Example 1 except that the Mg content was changed. Specifically, the value of c in Formula (F) is Fig.11 The hydrogen storage alloy was prepared in the manner of the values ​​shown. The hydrogen storage alloy powder was evaluated in the same manner as in Experimental Example 1 before activation.

[0238] A plurality of batteries (nickel-metal hydride storage batteries) were produced by the same method and conditions as those for producing battery A1 except that the obtained hydrogen storage alloy powder was used as the negative electrode active material.

[0239] Part of the preparation conditions and evaluation results of the hydrogen storage alloy and the evaluation results of the battery are shown in Fig.11 and Fig.12 It should be noted that Fig.11 and Fig.12 The results for battery A1 are also shown.

[0240] Batteries A26 to A31 are alkaline storage batteries (A) using hydrogen storage alloys (M). Fig.12 As shown, the charge-discharge cycle characteristics of batteries A26 and A27, whose c values ​​are greater than 0.01 and less than 0.10 (e.g., in the range of 0.02 to 0.09), are particularly high. The high-rate discharge characteristics at low and extremely low temperatures of batteries A30 and A31, whose c values ​​are greater than 0.20 and less than 0.30 (e.g., in the range of 0.21 to 0.28), are particularly high.

[0241] Industrial Applicability

[0242] The present disclosure can be used for alkaline storage batteries (eg, nickel-metal hydride storage batteries).

[0243] Description of Reference Numerals

[0244] 1 Negative electrode

[0245] 2 Positive electrode

[0246] 3 Diaphragm

[0247] 4 Battery housing

[0248] 7 Sealing body

[0249] 8 Insulation pad

[0250] 9 Positive electrode collector plate

[0251] 10 Alkaline batteries

[0252] 11 Alkaline electrolyte

Claims

1. A hydrogen storage alloy having a composition represented by the following formula (F): The a R (b-a) Mg c Zr d We x To y M z (F) R is at least one rare earth element including Y and excluding La; satisfies the formulas of 0.10≤a≤0.40, 0.67≤b≤0.96, 0.01≤c≤0.30, 0.01≤d≤0.05 and b+c+d=1.00; M is at least one element selected from Co, Mn, Ag and Sn; satisfies 3.10≤x≤3.80, 0.03≤y≤0.25, 0≤z≤0.05 and 3.45≤x+y+z≤3.85, As a crystalline phase, it includes a first phase, a second phase, a third phase and a fourth phase, wherein the first phase is selected from a phase having a Ce2Ni7 type structure, a phase having a Ce5Co 19 Phases with Pr5Co 19 The second phase is another phase selected from the phase group, the third phase is another phase selected from the phase group, and the fourth phase has a CaCu5-type structure. In the crystal phase, when the composition ratio of the first phase is α, the composition ratio of the second phase is β, the composition ratio of the third phase is γ, and the composition ratio of the fourth phase is δ, Satisfies δ<α, γ≤β≤α, 60≤α+β≤83, α / β≤15.0 and 1≤δ≤15, where, The unit of α, β, γ and δ is mass %.

2. The hydrogen storage alloy according to claim 1, wherein In the above formula (F), 0.01≤c<0.10 is satisfied.

3. The hydrogen storage alloy according to claim 1, wherein In the above formula (F), 0.20<c≤0.30 is satisfied. 4 . The hydrogen storage alloy according to claim 1 , wherein the average particle size thereof is in the range of 15 μm to 30 μm.

5. An alkaline storage battery comprising a positive electrode, a negative electrode and an alkaline electrolyte, wherein the negative electrode comprises a negative electrode active material, The negative electrode active material includes the hydrogen storage alloy according to any one of claims 1 to 4.

6. The alkaline storage battery according to claim 5, wherein Potassium hydroxide is dissolved in the alkaline electrolyte. The potassium concentration of the alkaline electrolyte is in the range of 5.5 mol / L to 8.0 mol / L.

7. The alkaline storage battery according to claim 5, wherein The mass saturation magnetization of the hydrogen storage alloy is in the range of 1.0 emu / g to 4.0 emu / g.

Citation Information

Patent Citations

  • Onkyosochi

    JP1976071114A

  • Method of bonding label to extruded polyethylene net sack

    JP1980012080A

  • Antilock controlling method

    JP1985061354A

  • Hydrogen storage alloy for alkaline storage battery, alkaline storage battery and its manufacturing method

    JP2008084649A